Factors influencing the ovarian response in intracytoplasmic sperm injection (ICSI) - Seyed Gholam Ali Jorsaraei; Maryam Gholamitabar Tabari; Yousef reza yousefnia pasha; Mahtab Zeinalzadeh; Ali asghar Beiky; Mahmod Hajiahmadi (Caspian Journal of Reproductive Medicine, 2017)
Background: Ovarian response to gonadotropin stimulation can predict the success rate of Assisted Reproductive Technology. The purpose of this study was not only to determine the ovarian response rate in patients on whom intracytoplasmic sperm injection (ICSI) did not successfully work but also to assess the influence of factors on ovarian response.